Numerical Study of Residual Stresses Due to External Cooling in Extruded Polymer Profiles. Issue 3 (12th January 2022) - Spanjaards, Michelle M. A.; Hulsen, Martien A.; Anderson, Patrick D.
Abstract: Profile extrusion is a production technique to make polymer profiles and hollow tubes. At a certain distance after the die exit the polymer extrudate is guided into a cooling chamber, where the polymer is cooled extensively to set the part dimensions. Uniform cooling in the cooling chamber is required to avoid warpage and twisting of the extrudate due to differential shrinkage. The effect of extrudate cooling on the shape of the extrudate and the residual stresses in the final extrudate product are numerically studied. Two different cases are studied: a 2D axisymmetric problem of a viscoelastic fluid exiting an annular die and a 3D problem of a hollow square shaped die. The extrudate is extensively cooled from a distance L c $L_{\text{c}}$ from the die exit. Extrudate cooling is modeled by subjecting the extrudate to heat loss via convection. For L die < z ≤ L c $L_{\text{die}}<z\le L_{\text{c}}$ the Nusselt number Nu is fixed to 1 to represent the part of the extrudate in between the die exit and the entrance of the cooling chamber. For z > L c $z>L_{\text{c}}$ the Nusselt number is varied to mimic different cooling speeds. The Weissenberg number Wi, the Nusselt number and L c $L_{\text{c}}$ are varied in this work. Results show that for high values of Wi a significant skin‐effect of high residual stresses appear near the extrudate edges for high Nusselt numbers and small values of L c $L_{\text{c}}$ . It is also shown that for high Weissenberg numbers the shape of the extrudate is significantly altered due to extrudate swell, when the extrudate is cooled slower. For fast cooling and small values of L c $L_{\text{c}}$, the polymer does not have time to relax and the elastic stresses are "frozen in." This leads to less extrudate swell but large residual stresses near the extrudate edges. Abstract : Profile extrusion is a production technique used to make hollow polymer profiles. After exiting the die, the extrudate is guided into a cooling chamber, where it is cooled to set its dimensions. Uniform cooling is required to avoid warpage. In this paper the effect of extrudate cooling on the shape and residual stresses in the final product are numerically studied.